Blood profile in cows from small farms with low productivity - Ježek, JozÌŒica; Nemec, Marija; Starič, Joze; Klinkon, Martina (Acta Agraria Kaposváriensis, 2010)
The aim of the study was to analyse the results of haematological and biochemical examinations of blood in cows from farms with low rearing intensity. The results of blood examinations from 51 cows were analysed. The cows originated from different small farms from south east part of Slovenia. In blood samples haematological and different biochemical variables were measured. The results were evaluated regarding the normal values for cattle. The descriptive statistics and percentage of cows deviating from normal values for investigated variables were calculated. The mean values of investigated variables were inside reference interval for cattle except the portion of eosinophils which was above the reference value. In 16.7% of cows haemoglobin concentration and in 31.0% haematocrit value was below the reference value. In 55.6% of cows eosinophilia was ascertained. The results of biochemical examination show that 45.2% of cows had a concentration of total serum protein, 28.8% a concentration of urea and 35.5% a concentration of serum iron below the reference value. Some deviations were observed also regarding the mineral status. The results indicate inappropriate diet of these cows and in many cases possible infestation with parasites. Better care in parasite control and a well balanced diet would increase production in such herds.
Keywords: cows; blood; haematology; biochemistry; low intensity of production